The problems of reducing temperatures in the district heating network - Sekret, Robert (Instal, 2021)
The paper presents current possibilities of reducing the supply and return temperature of the district heating network. The article also proposes possibilities of technological development in the field of low-temperature district heating systems. The paper indicates that intensive thermal modernization of buildings is the basis for improving the energy efficiency of district heating networks and systems. Thermo-modernization leads to lower temperatures of heating systems in buildings. Moreover, new energy standards of buildings allow buildings to be heated with heat from the return of the district heating networks. The article also explains that obtaining energy, ecological and economic effects of improving the district heating network is strongly dependent on network management based on the specific behavior of end users. This is the starting point for the development of intelligent district heating networks/systems.